A redox ruthenium compound directly targets PHD2 and inhibits the HIF1 pathway to reduce tumor angiogenesis independently of p53. (January 2019) - Vidimar, Vania; Licona, Cynthia; Cerón-Camacho, Ricardo; Guerin, Eric; Coliat, Pierre; Venkatasamy, Aina; Ali, Moussa; Guenot, Dominique; Le Lagadec, Ronan; Jung, Alain C.; Freund, Jean-Noel; Pfeffer, Michel; et al.
Abstract: Targeting specific tumor metabolic needs represents an actively investigated therapeutic strategy to bypass tumor resistance mechanisms. In this study, we describe an original approach to impact the cancer metabolism by exploiting the redox properties of a ruthenium organometallic compound. This organometallic complex induced p53-independent cytotoxicity and reduced size and vascularization of patients-derived tumor explants that are resistant to platinum drugs. At the molecular level, the ruthenium complex altered redox enzyme activities and the intracellular redox state by increasing the NAD+/NADH ratio and ROS levels. Pathway analysis pointed to HIF-1 as a top deregulated metabolite pathway. Unlike cisplatin, treatment with the ruthenium complex decreased HIF1A protein levels and expression of HIF1A target genes. The rapid downregulation of HIF1A protein levels involved a direct interaction of the ruthenium compound with the redox enzyme PHD2, a HIF1A master regulator. HIF1A inhibition led to decreased angiogenesis in patient-derived xenografted using fragments of primary human colon tumors. Altogether, our results show that a ruthenium compound impacts metabolic pathways acting as anticancer agents in colon cancer via an original mechanism of action that affects redox enzymes differently than platinum-based drugs. Highlights: An anticancer ruthenium complex exerts cytotoxic stress independently of p53 in colon cancer cells. Transcriptomic analyses show that it alters cancer metabolism, especially by the HIF1 pathway. The ruthenium complex reduces HIF1A protein level and HIF1A function by inducing the enzymatic activity of PHD2. The ruthenium complex inhibits tumor angiogenesis in vivo in xenografted human primary tumors.